2013
DOI: 10.1007/s11434-013-5709-2
|View full text |Cite
|
Sign up to set email alerts
|

Iodine biofortification of vegetable plants—An innovative method for iodine supplementation

Abstract: To elevate the iodine level in edible plants has been shown to be an excellent approach to correct iodine deficiency. We have proposed an innovative approach to produce iodine supplementation by growing vegetables on soils with algal-based iodized organic fertilizer. Ten species of vegetables were tested. The biological absorption and migration of the iodine within the vegetable plants were revealed using microscopy with silver iodide precipitation technique. The results show that the absorption of iodine by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 14 publications
4
45
0
Order By: Relevance
“…The variation in Si accumulation among species has been attributed to differences in the uptake ability of the roots . A species‐related accumulation was also reported for other micronutrients that used the shell for biofortification . The results of the present study confirm that, to obtain Si biofortified vegetables, the choice of appropriate species is important.…”
Section: Resultssupporting
confidence: 84%
“…The variation in Si accumulation among species has been attributed to differences in the uptake ability of the roots . A species‐related accumulation was also reported for other micronutrients that used the shell for biofortification . The results of the present study confirm that, to obtain Si biofortified vegetables, the choice of appropriate species is important.…”
Section: Resultssupporting
confidence: 84%
“…The previously published researches showed successful results of enrichment of spinach [26, 27] lettuce [28, 29] or pakchoi [30] with iodine. Weng et al [14] reported that the leafy vegetables store more iodine in edible tissues than the fruit vegetables, which is even about 70-fold more. Because of the controllable and efficient systems for crop growing, the hydroponic cultivation makes a great possibility for biofortification with iodine [29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is commonly known that after foliar application of KI on the surface of leaves, I − is absorbed by leaves [46]. The I − uptake by leaves remains mainly in their cells [46, 47], primarily attributable to the cell wall and organelles [14]. Absorption of iodine with these organic structures of plant tissues can be inhibited in the human or animal organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting considered in the work of Weng Y.X., Hong C. L., Xia T.H., Bao L.T., Liu H.P. and Ki D.W. technology for enriching plants with iodine using seaweed containing the organic form of a microelement as fertilizers (Weng et al 2013). We believe that this direction should be considered for implementation in the conditions of coastal marine territories of the North of Russia.…”
Section: Literature Reviewmentioning
confidence: 97%